THE FINANCIAL PERFORMANCE OF MANUFACTURING COMPANIES IN IDX AND SOME FACTORS THAT INFLUENCE - Ichsan, Ichsan; Silvia, Ira; Mahdawi, Mahdawi; Syamni, Ghazali (Jurnal Aplikasi Manajemen, 2021)
This study aims to examine some factors affecting the financial performance of manufacturing companies in the Indonesia Stock Exchange (IDX). This research uses data on the financial statements of 20 manufacturing companies listed on IDX in the period 20132017 and carried out share distribution facilities for their employees. This research model is a panel regression model done by testing the common effect model, fixed-effect model, and random effect model. Based on the Chow test and Hausman test, it is found that the best model in this study is the fixed effect model. The study results find that dividend policy, a share giving program to employees, and debt to equity ratio are significant factors affecting the financial performance of manufacturing companies in Indonesia. From these three factors, the debt to equity ratio is the dominant factor determining the financial performance of manufacturing companies, while investment decision does not significantly affect it. Future research studies can be carried out by focusing on other industrial sectors such as the Jakarta Islamic Index 70 and adding other macroeconomic variables.